Energy use for millet (Pennisetum glaucum (L) R. Br.) production in the large-scale rainfed schemes eastern Sudan - Yousif, Lotfie; M. Ali, Adam (Gezira Journal of Engineering and Applied Sciences, 2023)
Energy in agricultural production is used in different forms and ways to meet the increasing demand for food. The share of energy in agricultural production differs according to crops grown, production practices and sector. This study aimed to analyze energy input-output and to identify the energy use patterns for millet production in the large–scale rainfed agricultural schemes eastern Sudan. The required data was collect from 54 farmers through well designed questionnaire. The results showed that 30% of the surveyed farmers grew millet crop. The average grown area by farmers was 205 ha. The results showed that the total energy input used to produce millet was 1358.24 MJ ha -1 and the total energy output was 8557.90 MJ ha -1 . The results revealed that millet production was efficient in energy consumption; the energy ratio of output to input was higher than 1: 5. The average net energy, the energy productivity and the specific energy was 8699.66 MJ ha -1 , 0.43 kg MJ -1 and 2.35 MJ kg -1 , respectively. The results showed that the energy input for fuel was the highest among the other items of input energy. The use of stationary threshing in harvesting saved the direct energy by 219.63 MJ ha -1 compared to direct combine harvesting, but the former required additional 100.83 MJ ha -1 of manual energy. The results showed that, the more machinery is used in harvesting the more amount of the renewable energy is saved. The result indicated that the direct energy that used to produce the crop was greater compared to the indirect energy. Likewise, the non-renewable energy that used to produce the crop was greater than the renewable energy. The study concluded that more investigations are needed on balanced utilization of energy sources for millet production in the large-scale schemes in rainfed areas eastern Sudan.